Гібридні нейронні мережі з імунним навчанням для розв’язання задачі прогнозування часових рядів - Гніденко, В. А.; Звонкова, В. О. (ХНУРЕ, 2020)
This paper explores the principles of neural network hybridization and immune algorithms, which allows us to create new types of information processing models that have a higher quality of problem solving while reducing computational training costs. The use of hybrid neural networks for solving time series prediction is considered.
Keywords: штучна нейронна мережа; гібридна нейронна мережа; базова нейронна мережа; дисперсія